2016
DOI: 10.1002/polb.23986
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic properties and conformation of poly(3-hexylthiophene) in dilute solutions

Abstract: Conducting polymers demonstrate low solubility in organic solvents. Introducing aliphatic substituents into polymer chains improves their solubility, but may also lead to changes in conformational characteristics of macromolecules. In the present work, the studies of hydrodynamic properties and conformational characteristics of comb-shaped poly(3-hexylthiophene) with aliphatic side substituents were carried out in chloroform solutions. Conformational analysis of the studied macromolecules was performed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In the Table, the values of the persistence length and the Kuhn segment are also shown, calculated by substituting the obtained values of true〈Rg2true〉 and true〈Hendtoend2true〉 to eqs and , and by numerical solution of these equations for the Gromos, Amber, and OPLS‐AA force fields. Comparison of these results with the experimental data, obtained by McCulloch and Ho ( A exp = 6 ± 1 nm) and Yakimansky et al ( A exp = 6.0 ± 0.6 nm from rotational friction experiments and A exp = 6.7 ± 0.7 nm from translational friction experiments), suggests that the flexibility of P3HT chains is highly overestimated when using the OPLS‐AA force field. This fact confirms the earlier assumption that the model based on this force field describes the studied systems inadequately.…”
Section: Simulation Detailssupporting
confidence: 63%
“…In the Table, the values of the persistence length and the Kuhn segment are also shown, calculated by substituting the obtained values of true〈Rg2true〉 and true〈Hendtoend2true〉 to eqs and , and by numerical solution of these equations for the Gromos, Amber, and OPLS‐AA force fields. Comparison of these results with the experimental data, obtained by McCulloch and Ho ( A exp = 6 ± 1 nm) and Yakimansky et al ( A exp = 6.0 ± 0.6 nm from rotational friction experiments and A exp = 6.7 ± 0.7 nm from translational friction experiments), suggests that the flexibility of P3HT chains is highly overestimated when using the OPLS‐AA force field. This fact confirms the earlier assumption that the model based on this force field describes the studied systems inadequately.…”
Section: Simulation Detailssupporting
confidence: 63%
“…To the best of our knowledge, the conformational properties of RR-P3HT have been examined only in solutions 40,52,78 of rather good solvents, and thus, they cannot be used for direct comparison with the MD results of the present study; nonetheless, they can serve as a guide for a qualitative evaluation of the simulation data. Yakimansky et al 78 measured the monomer repeat unit length of P3HT in chloroform using dynamic light scattering (DLS) and found it to be equal to 3.7 Å at 298 K. Heffner and Pearson 52 examined dilute P3HT solutions using DLS, gel permeation chromatography, and viscosity measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it may be concluded that the Kuhn model gives neither real mass distribution within molecules nor realistic conformations of P3HT chains. In Yakimansky et al . an attempt was made to compensate this inadequacy of the Kuhn model, using the d V value (determined from the partial specific volume of a polymer trueυ) instead of the segment hydrodynamic diameter d Kuhn .…”
Section: Resultsmentioning
confidence: 99%